A Congruous Model of Matrilineal Culture Inheritance - Dwi Rini Sovia Firdaus (FISIP Universitas Atma Jaya Yogyakarta, 2022)
De Fleur's communication model inserts the mass media device, gives the possibility to two-way feedback, and stated that noise might occur at any stage. In contrast, the flowthing model introduced by Al-Fedaghi describes the information flow. This research adapts both concepts to produce cultural inheritance communication models. Minangkabau was chosen because of its unique matrilineal cultural pattern, where customary leaders take part in the wider family communication besides the role of the father and the mother. All concepts inculcate the soul of leadership, entrepreneurial spirit, and high social spirit. This answers the stereotype of Minangkabau people as hard-working entrepreneurs.